Implementasi Aplikasi Surat Online Berbasis Web Pada Perangkat Desa Mantingan - Muhammad Ali Subkan (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
Technology that is increasingly developing in the modern era has given rise to various innovations provided by students, society and scientists with the aim of making human life easier. The innovations that are present are expected to help people live their daily lives. But unfortunately innovations that make human work easier are currently not that massive, especially in the field of population data. Manual data processing has so far given rise to problems due to human error. Humans make many mistakes in various circumstances. Data related to population administration, which is the process of submitting letters involving population data in several areas, especially in Mantingan Village, is still carried out manually. Apart from that, when data is entered into a letter archive, the time required becomes longer and sometimes it is even lost and damaged during natural disasters such as landslides, earthquakes and floods. Population document files which are manual in nature can be damaged and take a long time to re-register the data. The problems given initiated the author to propose a technology-based population letter system. This web-based online letter making application is useful in supporting the creation of population letter certificates with the main functionality, namely processing population administration applications more efficiently. The creation of this web-based online letter program is the result of collaboration between the Balekambang Jepara Polytechnic and the Mantingan Village Government, Tahunan Regency District. .